2015
DOI: 10.1039/c5cy00168d
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium catalyzed one-step hydroamidation of cyclopentadiene and dicyclopentadiene

Abstract: A one-step rhodium catalyzed direct route from alkene to amide is presented via the hydroamidation reaction of cyclopentadiene and dicyclopentadiene with pyrrolidine. A homogeneous catalyst of ijRhIJcod)Cl] 2 without additional phosphorus ligands was established giving a 90% yield of the respective monoamide species of Dcpd with a high TOF of 1060 h −1 . An important side reaction in hydroamidation reactions is the formation of oligomers of dicyclopentadiene. This unwanted reaction could be overcome by the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Behr et al already showed the possibility to reduce the dimerization process by the use of tertiary amines as additives, 57 which have a high coordination ability to the metal center 62 as well as to the C-C double bond. Behr et al already showed the possibility to reduce the dimerization process by the use of tertiary amines as additives, 57 which have a high coordination ability to the metal center 62 as well as to the C-C double bond.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behr et al already showed the possibility to reduce the dimerization process by the use of tertiary amines as additives, 57 which have a high coordination ability to the metal center 62 as well as to the C-C double bond. Behr et al already showed the possibility to reduce the dimerization process by the use of tertiary amines as additives, 57 which have a high coordination ability to the metal center 62 as well as to the C-C double bond.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42] In contrast just a few investigations with dienes as starting materials for the HAM can be found in the literature, among them the rhodium-catalyzed formation of diamines from a,u-diolens using [Rh(cod)Cl] 2 , 43 conversion of limonene with various amines 44 and reaction of isoprene in an aqueous two-phase system. 57 Therefore, the initial step of the HAM, e.g. 46 Till now only a few technical applications for Cpd are known.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of competing dimerization is demonstrated by the aminocarbonylation of cyclopentadiene developed in our laboratories . The desired amides of cyclopentadiene were formed only in small amounts under rhodium catalysis with pyrrolidine as the amine component.…”
Section: C5 Moleculesmentioning
confidence: 99%
“…The effect of competing dimerization is demonstrated by the aminocarbonylation of cyclopentadiene developed in our laboratories. [87] The desired amides of cyclopentadiene were formed only in small amounts under rhodium catalysis with pyrrolidine as the amine component. Monosubstituted amides of dicyclopentadiene were the main products formed by in situ dimerization of cyclopentadiene followed by aminocarbonylation ( Figure 39).…”
Section: Carbonylationmentioning
confidence: 99%
“…This behavior is simply explained by the stronger basicity of aliphatic amines:F or example,a lanine ester (pK b = 4.87), benzylamine (pK b = 4.66), and piperidine (pK b = 2.78) are much more basic than aniline (pK b = 9.37; Scheme 1a). [15] Notably,b oth catalyst systems favor the formation of the linear amides from olefins and aliphatic amines.In contrast, the formation of the branched amides from carbonylation reactions is more challenging because of the increase in steric effects for the olefin insertion into the palladiumhydride bond to form the secondary carbon palladium intermediates E (Scheme 1b). To overcome this problem, Huang and co-workers developed an elegant strategy to utilize aminals as surrogates of aliphatic amines.…”
mentioning
confidence: 99%